2020
DOI: 10.1088/1757-899x/864/1/012101
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Khaya Senegalensis Raw Feedstock Particle Sizes On Solid Fuel Pellet Quality

Abstract: In recent years, the usage and demand for biomass pellet has been increasing due to the need of substitution for non-renewable energy source. Therefore, high quality solid fuel is in need to cater this demand. Pellet qualities such as durability, calorific value and density are different depending on the type of material, size of particle and the density of the feedstock. In this study, the durability, calorific value and unit density of Khaya Senegalensis pellet was investigated. This was done to identify the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…The study by [7] investigated the effects of biomass moisture content (MC=14-20%) and pelletization temperature (T=50-80 °C) on lower heating value (LHV) and energy density, pine sawdust pellet quality using response surface methodology. In this particular study, the results obtained are consistent with the values of calorific value gained from [17], which showed that the calorific value ranges from 15.222 MJ/kg to 16.503 MJ/kg from different particle sizes.…”
Section: Effect Of Variables On Calorific Valuesupporting
confidence: 87%
See 1 more Smart Citation
“…The study by [7] investigated the effects of biomass moisture content (MC=14-20%) and pelletization temperature (T=50-80 °C) on lower heating value (LHV) and energy density, pine sawdust pellet quality using response surface methodology. In this particular study, the results obtained are consistent with the values of calorific value gained from [17], which showed that the calorific value ranges from 15.222 MJ/kg to 16.503 MJ/kg from different particle sizes.…”
Section: Effect Of Variables On Calorific Valuesupporting
confidence: 87%
“…Water plays a crucial role in the pelletizing process, acting as both a lubricant and a binding agent for the pellet [3,4]. Smaller particles have smaller gaps between them, whereas larger particles have larger gaps, making the smaller particles stronger than the larger particles [5,6]. Therefore, the primary objective of this research was to assess the effect of particle size and moisture content on the quality of fuel pellets.…”
Section: Introductionmentioning
confidence: 99%